Urine Output as a Non-Invasive Marker of Intracranial Pressure Changes After Furosemide in Craniotomy Patients - Putri, Febby Oktaviani; Khasanah, Furaida; Harmilah; Ghofur, Abdul; Suryani, Eko (poltekkes kemenkes mataram, 2025)
Craniotomy is a common surgical procedure in the neurosurgery division that involves making a sufficient hole in the cranium for optimal intracranial access. An important part of craniotomy is the maintenance of stable intracranial pressure by administering furosemide. The purpose of this administration is to observe changes in urine output. Objective to know the relationship between furosemide administration and changes in urine output volume of craniotomy patients at Hospital Tegal. This study was analytic observational with cross sectional approach. The sampling technique used total sampling with a total of 31 respondents. Data analysis using fisher excat test. The results of this study showed that most patients experienced changes in urine output volume of 27 respondents (87.1%) with an average change in urine from 245.8 ml to 1469.3 ml. There is a statistically significant relationship between furosemide administration and changes in urine output volume of craniotomy patients with the fisher exact test obtained a value of r = 0.013, so that alternative hypothesis can be accepted. The Conclusion there is a relationship between furosemide administration and changes in urine output volume of craniotomy patients at hospital in Tegal City.